2013
DOI: 10.5114/jcb.2013.37941
|View full text |Cite
|
Sign up to set email alerts
|

Permanent prostate brachytherapy extracapsular radiation dose distributions: analysis of a multi-institutional database

Abstract: PurposePeriprostatic brachytherapy doses impact biochemical control. In this study, we evaluate extracapsular volumetric dosimetry following permanent prostate brachytherapy in patients entered in a multi-institutional community database.Material and methodsIn the database, 4547 patients underwent brachytherapy (3094 – 125I, 1437 – 103Pd and 16 – 131Cs). Using the originally determined prostate volume, a 5 mm, 3-dimensional peri-prostatic anulus was constructed around the prostate (except for a 2 mm posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…In a multi-institutional analysis of 4547 patients, Merrick et al . found that the V 100 was less at the base (51.5%) and anterior (45.7%) of the gland when compared to the lateral (68.8%), posterior (75%), and mid gland (65.9%) [21]. We postulate that increased perirectal and periprostatic fat in patients with higher BMI values may lead to difficulties accessing the anterior prostate, thereby resulting in an inferior D 90 .…”
Section: Discussionmentioning
confidence: 94%
“…In a multi-institutional analysis of 4547 patients, Merrick et al . found that the V 100 was less at the base (51.5%) and anterior (45.7%) of the gland when compared to the lateral (68.8%), posterior (75%), and mid gland (65.9%) [21]. We postulate that increased perirectal and periprostatic fat in patients with higher BMI values may lead to difficulties accessing the anterior prostate, thereby resulting in an inferior D 90 .…”
Section: Discussionmentioning
confidence: 94%
“…Merrick et al (21) analyzed permanent prostate brachytherapy extracapsular radiation dose distributions in a multi-institutional database and found that the overall mean V 100 for the periprostatic annulus was 62.8%. The authors concluded that in multi-institutional community health centers, periprostatic annular doses are not as robust as those in selected high-volume brachytherapy centers and may be inadequate for optimal biochemical control after monotherapeutic brachytherapy, especially in high-risk patients (21).…”
Section: Discussionmentioning
confidence: 98%
“…The authors concluded that in multi-institutional community health centers, periprostatic annular doses are not as robust as those in selected high-volume brachytherapy centers and may be inadequate for optimal biochemical control after monotherapeutic brachytherapy, especially in high-risk patients (21). Merrick et al (22) evaluated the postimplant 5 mm, three-dimensional periprostatic annulus dosimetric coverage using CT scan within 2 h of the prostate seed implantation procedure.…”
Section: Discussionmentioning
confidence: 98%
“…Merrick et al . [ 7 ] reported in a series of 4547 patients a significant underdosage in the first 5 mm outside the prostate in patients treated with brachytherapy. They describe a V 100 (the volume of prostate receiving the prescription dose) as low as 45% in this 5 mm annulus.…”
Section: Discussionmentioning
confidence: 99%